Tratamento primário do efluente proveniente de uma indústria de abate de aves utilizando diferentes coagulantes - Rodrigues, André da Silva (2023)
Food industries use a considerable amount of water throughout their production process, in the case of poultry slaughterhouses it is no different, water consumption is present from the arrival of the birds in the industry until their departure for commercialization, due to this high water consumption a large volume of industrial liquid effluent is generated, the treatment of these types of effluents occurs using physical-chemical treatment methods followed by biological methods. This study aimed to analyze and evaluate the use of inorganic and organic coagulants in the primary treatment of effluent, in addition to analyzing the acidity of flotation oil from a poultry slaughtering industry in the municipality of Cascavel-PR. In this work, Magnofloc LT 7990 coagulants and ferric sulfate were used. Firstly, a survey was carried out on how effluent from a poultry slaughterhouse is generated, analyzing which characteristics are striking in the effluent generated. To characterize the effluent, collections were made during four months of production, the collected materials were sent for physical-chemical analysis of the effluent before and after treatment with the two coagulants. With the inorganic coagulant, ferric sulfate, an average removal of organic matter parameters (BOD and COD) of around 80% was obtained, while in relation to turbidity the removal was close to 95%. With the organic coagulant, the BOD and COD removal values were lower than those of the inorganic coagulant, something close to 75% removal, but on the other hand, the turbidity removal was 98%. It was demonstrated in this study that both coagulants presented similar removal efficiency values, with the organic coagulant there was a significant improvement in the removal of turbidity and an improvement in the acidity of the floated oil from the sludge generated with the coagulant, it is suggested to carry out further studies related to the generation of by-products with organic coagulants, such as sludge and float oil, as well as their economic potential.